Learning and developing critical consciousness through activism experiences : a comparative study - Tuğcu, İrem Ege. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
The aim of this study is to examine the learning and development of Freire’s (1974) critical consciousness through activism practices by focusing on LGBTQ+ activism in Turkey. Learning experiences and critical consciousness development were revealed comparatively by analyzing LGBTIQ+ activists, who stand up against social injustice and discrimination, and non- activist, who are LGBTIQ+ individuals. In this qualitative study, biographical interviews were conducted with six participants, their narratives were analyzed through the Documentary Method to reveal their orientation frameworks. The orientations of activists were clearly distinguished from non activist participants through accessing information sources, joining a community to learn by joining a community and developing motivation for learning. The components of critical consciousness, which are critical reflection, critical motivation, and critical action, varied between activist and non-activist participants. Unlike non-activists, the components of critical consciousness were encountered in the orientations of activist participants. The presence of all these components together demonstrated that activists were in the process of developing critical consciousness.
Keywords: Critical pedagogy.; Communication in education.; Gay liberation movement.